Utilization of the Agricultural Sector as Supporting the Economy in Loklahung Village, Loksado District, Hulu Sungai Selatan Regency, South Kalimantan Province - Eli Karliani; Ermi Maria Sihombing; Renold Aprilando Simamora; Santy Permata Sary Sihombing; Wina Anjelina (CV. Rayyan Dwi Bharata, 2023)
This study aims to describe how the role of agriculture in advancing the economy in Loklahung Village and describe it. In collecting data, researchers conducted interviews and observations in Loklahung Village, Loksado District, Hulu Sungai Selatan Regency, South Kalimantan Province. Based on the research conducted, the approach used is through a qualitative approach. This means that the data collected is not in the form of numbers, but the data comes from interview scripts, field notes, and other official documents, so this qualitative aims to describe the empirical reality divided by phenomena in depth, detail and detail. whole. This study aims to identify the potential of the agricultural sector as an economic driver in a region. The agricultural sector has played a role in the national economy through the formation of GRDP, earning foreign exchange, providing food and industry, alleviating poverty, creating jobs, and increasing people's income. The majority of the people of Loklahung village work as farmers, according to sources 85% of the people of Loklahung village work as farmers.